2017
DOI: 10.3906/kim-1607-5
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-enhanced Fenton-like degradation by surface-modified metal--organic frameworks as a promising method for removal of dye from aqueous samples

Abstract: Abstract:In the current research, the sulfonated metal-organic framework loaded on iron oxide nanoparticles, Fe 3 O 4 @MIL-100(Fe)-OSO 3 H, has been synthesized and utilized as a Fenton-like catalyst for the decolorization of aqueous solutions containing methyl orange (MO) dye as a model organic pollutant. The morphology and structure of the catalyst were characterized by X-ray powder diffraction, transmission electron microscopy, Brunauer-Emmett-Teller analysis, thermogravimetric analysis, Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
(52 reference statements)
1
6
1
Order By: Relevance
“…Also, the EDS spectrum represented the corporation of Fe ions in MIL-100(Fe) structure (Figure S2c and Table S2). These values are close to the reported values for MOFs [11]. The total pore volume of MIL-100(Fe) and MIL-100(Fe)/FA are estimated to be 0.32 and 0.13 cm 3 /g, and the pore size distribution of MIL-100(Fe) and MIL-100(Fe)/FA are observed at 24.20 and 20.06 Å.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Also, the EDS spectrum represented the corporation of Fe ions in MIL-100(Fe) structure (Figure S2c and Table S2). These values are close to the reported values for MOFs [11]. The total pore volume of MIL-100(Fe) and MIL-100(Fe)/FA are estimated to be 0.32 and 0.13 cm 3 /g, and the pore size distribution of MIL-100(Fe) and MIL-100(Fe)/FA are observed at 24.20 and 20.06 Å.…”
Section: Resultssupporting
confidence: 87%
“…Dual armed therapy and real-time monitored treatment trends of tumors called "theranostics" have gained attention in modern cancer treatment [11][12][13]. Moreover, using smart molecules for targeting, so-called "active targeting," in a nanoscale package harbors both selective tissue internalization and enhanced permeability and retention (EPR) effects of "passive targeting" which mainly accumulates the drug in tumor areas [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In heterogeneous processes, Fenton reactions are also favored under acidic conditions, since in alkaline conditions, decomposition of H 2 O 2 to H 2 O and O 2 is favored decreasing its concentration for Fenton reaction, which highest effectiveness is in the pH range 3.0-6.0. [56][57][58] Surprisingly, in the present study, the discoloration efficiency of AR8 decreased only slightly with increase of pH with no significant difference between pH 2.6-5.6 (t test, P = 0.05; Figure 7a) achieving total discoloration after 60 min. However, with further pH increase to 7.2, a slower degradation was evident.…”
Section: Effect Of Initial Phcontrasting
confidence: 60%
“…Recent studies have shown that, in the presence of hydrogen peroxide, MOF-based Fenton-like processes can be very effective in removing organic pollutants, including Methylene blue, Rhodamine B, phenol, and pharmaceuticals. ,,,, Most reactions can be performed under a wide pH range. , In the presence of visible light and H 2 O 2 , the catalytic performance of MIL-53­(Fe) can be improved significantly . This enhancement can be evaluated by using the synergetic index: SI = k MVH /( k MH + k MV ).…”
Section: Mof-based Advanced Oxidation Processmentioning
confidence: 99%